EFFECT OF ADDITIVE LEVEL ON THE SURFACE OF DIESEL ENGINE CYLINDER LINER - Kaleli, H.; Bektas, D. (SCIBULCOM LTD, 2011)
In this research the surface of the cylinder liner was examined from metallurgical standpoints, using specimens cut from real engine component (single cylinder diesel engine liner operated 22 h), in order to identify the effect and level of the additives formed on the rubbed surface. The surface of this liner is examined in three sections such as top dead center (TDC), middle dead center (MC) and bottom dead center (BDC). As a result, high amounts of additives were found at the TDC and they decrease through the MC then become nil at the BDC. X-ray diffraction analysis showed that the additives were situated as islands in the wear track.
Keywords: engine cylinder liner; additives level; Engineering